1979
DOI: 10.1079/bjn19790066
|View full text |Cite
|
Sign up to set email alerts
|

A new in vitro method for the estimation of digestibility using the intestinal fluid of the pig

Abstract: I . A new in vitro method using the intestinal fluid of the pig for predicting the digestibility of diets was proposed.2. A 0.5 g sample of pig diet was placed in a IOO ml Erlenmeyer flask, 20 mg pepsin (EC 3 . 4 . 4 . I ) in 10 rnlo.075 M-hydrochloric acid was added, and the mixture was incubated for 4 h at 37". Then, after neutralization with 0.2 M-sodium hydroxide, 10 ml of intestinal fluid was added and incubated for an additional 4 h at 37". This fluid was obtained from a pig fitted with a simple cannula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 9 publications
0
51
0
Order By: Relevance
“…These workers used a more dilute solution of pepsin (0-002% (weight/volume)) than that used in this trial (0-2% weight/volume), so their test was likely to have been of greater sensitivity (Johnston and Coon, 1979b). Other workers have extended the pepsin test to include an incubation in pancreatin (Furuya, Sakamoto and Takahashi, 1979;Clunies and Leeson, 1984) and found good correlation of the results with nitrogen digestibility measured in vivo. The relative success of these in vitro methods as cheap, yet sound indices of nitrogen digestibility highlights the necessity for further study of the relationships between the digestibilities of nitrogen and those of the key essential amino acids, with the eventual objective of being able to predict amino acid digestibility from nitrogen digestibility measured in vitro.…”
Section: Digestibility Trialsmentioning
confidence: 87%
“…These workers used a more dilute solution of pepsin (0-002% (weight/volume)) than that used in this trial (0-2% weight/volume), so their test was likely to have been of greater sensitivity (Johnston and Coon, 1979b). Other workers have extended the pepsin test to include an incubation in pancreatin (Furuya, Sakamoto and Takahashi, 1979;Clunies and Leeson, 1984) and found good correlation of the results with nitrogen digestibility measured in vivo. The relative success of these in vitro methods as cheap, yet sound indices of nitrogen digestibility highlights the necessity for further study of the relationships between the digestibilities of nitrogen and those of the key essential amino acids, with the eventual objective of being able to predict amino acid digestibility from nitrogen digestibility measured in vitro.…”
Section: Digestibility Trialsmentioning
confidence: 87%
“…However, several multi-enzyme methods have been investigated in detail. Graham et al (1989) The results with the pepsin-jejunal fluid method were found to be closely correlated to faecal digestibility of protein and dry matter in pigs (Furuya et al 1979) and in poultry (Sakamoto et al 1980). Dierick et al (1985) compared results obtained with the pepsin-jejunal method with results from two other two-step in vitro methods, both including pepsin in the first step, but one using pancreatin and the other pronase in the second step.…”
Section: Resultsmentioning
confidence: 99%
“…A two-step incubation with pepsin digestion for 4 h followed by a further 4-h digestion with pig jejunal fluid was developed by Furuya et al (1979). The method was used for measuring in vitro digestibility of protein and dry matter.…”
Section: Methodsmentioning
confidence: 99%
“…The SFD treatment was adapted from the method of Furuya et al (1979), whereby of 20 ml of pepsin HCl (0.075 mol l -1 HCl; 2 mg pepsin ml Substrate combinations were fermented in vitro with an equine faecal inoculum using the in vitro gas production (GP) technique of Theodorou et al (1994). Methods employed for the GP technique were as described by Theodorou et al (1994); each bottle contained 85ml…”
mentioning
confidence: 99%